Analysis of Live Shopping on E-Commerce Platforms as an Interactive Marketing Communication Strategy n The Digital Economy Era - Berkat Jaya Nehe; Eben Ezer Buulolo; Magdalena Laia; Tuti Herlis Wau; Ofranis Bago; Umarudin Laia; Meri Kristina Halawa (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
The transformation of the digital economy has significantly reshaped marketing communication strategies, particularly through the emergence of live shopping on e-commerce platforms. This study aims to examine how interactive marketing communication in live shopping fosters social presence, enhances consumer trust, and stimulates impulse buying behavior. Employing a qualitative approach, the research utilizes participatory observation and in-depth interviews conducted during live shopping sessions on major Indonesian e-commerce platforms. The findings reveal that the effectiveness of live shopping is driven by the integration of several key elements, including real-time interactivity, host social presence, entertainment (shoppertainment), parasocial interaction, and the strategic use of platform features. These elements collectively reduce consumers’ psychological barriers to online shopping and create a more humanized and participatory shopping experience. Nevertheless, the study also identifies challenges related to maintaining brand message consistency amid the highly dynamic nature of two-way communication. This research contributes theoretically to the field of digital marketing communication and offers practical insights for brands in designing effective and sustainable live shopping strategies within competitive digital ecosystems.